DINAMIKA PEMBATALAN PUTUSAN BASYARNAS PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 3 TAHUN 2006 - ahmad nurozi (Mahkamah : Jurnal Kajian Hukum Islam, 2016)
ABSTRACTDYNAMICS OF THE CANCELLATION OF BASYARNAS AFTER THE ENACTMENT OF LAW NO. 3 OF 2006  The development of sharia economy in Indonesia is not supported by adequate legal tools.  As a result, disputes often arising between parties cannot be resolved by both litigation and non-litigation even though the legal policy has been enacted in Law No. 3 of 2006 on the amendment of Law No. 7 of 1989 on religious courts that governs and broadens the absolute competence of religious courts in sharia economic matters.The purpose of the study was to identify the dynamics of the cancellation of national sharia arbitration’s decisions (BASYARNAS) after the enactment of Law No. 3 of 2006.The research method used the normative-sociological approach with Article 49 of Law No. 3 of 2006 on the authority of religious courts in resolving sharia economic disputes and several corresponding laws as the research subject.The primary, secondary and tertiary data were obtained through the study of documents using content analysis with the researcher himself as the research instrument.The results of this study show that there are dynamics in the process of cancellation of the national sharia arbitration’s decisions (BASYARNAS) after the enactment of Law No. 3 of 2006.  There had been a reduction in the role of religious courts to resolve disputes through arbitration,  which is the authority to execute the decisions of BASYARNAS.  The aforementioned role had been taken over by the district courts,  particularly in terms of cancellation of BASYARNAS’s decisions. In addition, the legal basis for the district courts to receive and examine the request to cancel BASYARNAS’s decisions is contrary to the theory of law formation as stipulated in the laws and regulations dated 12 August 2011.Furthermore,  one of the references of Indonesian legal system is the principle of lex posteriori derogat legi priori.  Therefore,  Law number 30 of 1999 on arbitration and dispute alternative resolution particularly Article 72 Paragraph (2) is no longer valid after the enactment of Law No. 3 of 2006.Keywords: Sharia Economy, Arbitration, Cancellation, Religious Courts